Endogenous NO-mediated transcripts involved in photosynthesis and carbohydrate metabolism in alfalfa (Medicago sativa L.) seedlings under drought stress - Zhao, Ying (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.